Investigation of the Effects of Alkaline Treatment on the Properties of Poly(3,4-ethylenedioxythiophene):Poly(4-styrenesulfonate) Films - Li, Jiao; Zhang, Hua; Liu, Juncheng; Qi, Hui (Asian Journal of Chemistry, 2012)
In this article, the influence of sodium hydroxide treatment on the properties of poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) films has been investigated. We have also examined the performance of organic solar cells with the un-doped and NaOH-doped PEDOT:PSS layer. Results show that the acidity of PEDOT:PSS solution can be remarkably reduced by adding the NaOH solution with the optimal doping concentration (£ 0.43 wt %), while the NaOH-doped PEDOT:PSS film shows an improved optical transmission and unchanged conductivity. However, compared with the pristine organic solar cell without adding NaOH to the whole-extraction layer, the NaOH-doped organic solar cell shows a slightly degraded in the power conversion efficiency (from 2.12 to 2.01 %), which has been attributed to the decreased Voc and fill factor of the devices after the addition of NaOH.